2014
DOI: 10.1155/2014/435983
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Abnormalities in Chronic Lymphocytic Leukemia: Where We Are and Where We Go

Abstract: Chromosomal abnormalities in chronic lymphocytic leukemia (CLL) are detected in up to 80% of patients. Among them, deletions of 11q, 13q, 17p, and trisomy 12 have a known prognostic value and play an important role in CLL pathogenesis and evolution, determining patients outcome and therapeutic strategies. Standard methods used to identify these genomic aberrations include both conventional G-banding cytogenetics (CGC) and fluorescence in situ hybridization (FISH). Although FISH analyses have been implemented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
122
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 117 publications
(208 reference statements)
5
122
0
4
Order By: Relevance
“…Biallelic deletion of 13q14 was observed in 17% of the cases with both DNA probes D13S25 and D13S319, which is in the range reported previously [Garg et al, 2012]. The occurrence of trisomy 12, del (11) [Fabris et al, 2011;Ouilette et al, 2011;Véronèse et al, 2013;Xu et al, 2013;Puiggros et al, 2014;Stevens-Kroef et al, 2014]. However, these new assays share several limitations: the inability to detect balanced rearrangements, low-level mosaicism, and a clonal evolution of neoplastic B cells.…”
Section: Discussionmentioning
confidence: 77%
“…Biallelic deletion of 13q14 was observed in 17% of the cases with both DNA probes D13S25 and D13S319, which is in the range reported previously [Garg et al, 2012]. The occurrence of trisomy 12, del (11) [Fabris et al, 2011;Ouilette et al, 2011;Véronèse et al, 2013;Xu et al, 2013;Puiggros et al, 2014;Stevens-Kroef et al, 2014]. However, these new assays share several limitations: the inability to detect balanced rearrangements, low-level mosaicism, and a clonal evolution of neoplastic B cells.…”
Section: Discussionmentioning
confidence: 77%
“…BIRC2/3-NIK signaling target effectors contribute directly to carcinogenesis (Yamato et al, 2015). It has been reported that chronic lymphocytic leukemia has BIRC3-associated abnormalities (Puiggros et al, 2014). Moreover, some researchers have suggested that Lynch syndrome and sporadic ovarian cancers differ by several deregulated genes such as BIRC3 (Jönsson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some genetical abnormalities are associated with bad prognosis. Especially, 11q, 13q, 17p deletions and trisomy 12 are important for prognosis (1,2). Firstly, 17p deletion was diagnosed in our patient using FISH method.…”
Section: Introductionmentioning
confidence: 95%